“La comprensión literal de textos argumentativos en estudiantes de Educación Básica Media” - Torres Troncos, Elizabeth Rosario (2024)
The present study analyzes the levels of development in the literal comprehension of argumentative texts related to lexis and vocabulary, key words and key ideas, in students of Secondary Basic Education. It is an exploratory and quantitative study. A questionnaire was applied to 114 seventh grade students. Performance was measured in three dimensions: lexical and vocabulary, key words and key ideas. In lexis and vocabulary, 73% were in the poor category. In key words, 65% are in the good category. In key ideas, 58% are in the bad category. It is concluded, at a global level, that the literal level has a performance of 45% in the good category. Difficulties were identified in the performance related to lexis and vocabulary and key ideas. It is recommended to implement focused strategies to improve vocabulary management, identification of key words and synthesis of main ideas.